The Art Education Drawing on Configuration of Art Education: Philosophy Perspective - Sunarto,; Irfanda Rizki Harmono Sejati, (Technium Social Sciences Journal, 2020)
This article discusses about drawing on configuration of art education, a philosophy perspective. Drawing is discussed philosophically which is based on: ontology, epistemology, and axiology. Drawing is a work of fine arts. Drawing can be defined as a picture or diagram which is drowned by using pencil, pen or painting crayon, especially a monochrome picture. From philosophical side, drawing has a “truth”. Drawing that comes pure from mind represent a shape of two dimensional look. Education; drawing will form honesty (Logico Aestheticus) and truth (Logico Mathematicus). Ontologically (intrinsic substance), drawing actually is observing a shape detail and will relate to thought from science perspective and other knowledge towards object observation.